Evaluation of the achievement development program of the dki jakarta province softball sports - Aryono Fajar Harianto; Ika Novitaria Marani; Susilo S (Gladi : Jurnal Ilmu Keolahragaan, 2023)
This research aims to obtain facts, data, and information about the results of the evaluation of the achievement coaching program for the women's softball sports of DKI Jakarta Province. This study used evaluative methods with the CIPP model. Data collection techniques use questionnaires, documentation, observations, and interviews. The subjects of this study are The Core Board, Coach, and Athlete. The results revealed that the context component of the Pengprov Perbasasi DKI Jakarta already has a long-term, medium, and short-term plan. However, the DKI Jakarta Provincial Women's Softball Team was only able to achieve the goal of the achievement coaching program at the 2018 Softball National Tournament. The input components, facilities, equipment, and equipment provided are enough to meet the needs of the DKI Jakarta Provincial Women's Softball Team. However, the need for supplements and vitamins for new athletes ahead of the implementation of PON. In the process component, the coaching staff implements a walking selection system and promotes and degrades athletes based on batting average data, left on base, running base in, accumulation of errors, & success in sacrifice. The training process was carried out face-to-face and virtually during the Covid-19 pandemic. In the product component, the results obtained by the DKI Jakarta Provincial Women's Softball Team during the period 2018 to 2022 were finalists in the 2018 Softball National Tournament. However, in the 2019 PON Qualification and PON XX Papua in 2021, the DKI Jakarta Provincial Women's Softball Team was only able to rank fifth